A socio-ecological analysis of environmental change in the Kannaland Municipality of the Klein Karoo, South Africa, over the last 100 years - Murray, Amy Louise (Department of Environmental and Geographical Science, 2016)
This study utilizes a cyclical socio-ecological systems approach to explore change in natural vegetation and land use within the Kannaland Municipality of the Klein Karoo. Repeat ground photography, historical climate and agricultural data, and in-depth, semi-structured interviews were used to assess environmental, political and socio-economic change in the study area since the early 1900s. Few studies have had the opportunity to augment the analysis of repeat ground photography with contextual information from in-depth interviews making this study unique in its approach. For most of the 20th century agricultural land use within the Klein Karoo has undergone fluctuations of increased and decreased productivity. However, during the later decades a noticeable decline in agricultural land use, especially sheep and goat production, has been recorded. Largely due to this, and contrary to degradation projections for this area, evidence of growth in cover of natural vegetation, especially over the last 20 years, was found. From the mid 1990s change from largely agricultural to recreational game and weekend farming as well as tourism-related land use has increased. Implications of recent land use change are perceived as both positive and negative. Increases in natural vegetation cover and potential associated biodiversity improvements are considered positive implications associated with the demise in extensive agricultural land use for the area. A decline in farm-based employment and agricultural productivity are considered negative implications of this land use change. Substantial increase in game farming within the study area is perceived to require stringent monitoring and research into the long term implications of this land use on natural vegetation. For optimal land use management and conservation of natural vegetation this study recommends building the capacity of the agricultural and conservation extension services within the Klein Karoo. The study further promotes the diversification of land use inclusive of agricultural production, conservation of biodiversity and development, particularly within the tourism sector, as optimal for the sustainability of land use in the Klein Karoo.